Risk Factors Causing Stunting in the Community at Sicanang Health Center - Lubis, Dita Anggriani; Br Gultom, Ria Fazelita; Hidayati, Yusmalia; Girsang, Rut Yohana; Sipayung, Novitri; Meidita, Dinda Dian (PT Inovasi Pratama Internasional, 2025)
Stunting is the inadequate intake of nutrients from the womb in children until the age of five, which is characterized by stunted height. As a result of these chronic malnutrition conditions, it can systemically inhibit the development of children in the first two years of life so that children become stunted. This study is a quantitative study with a cross-sectional design conducted at the Sicanang Medan Health Center. For respondent collection, the sampling procedure was carried out using the total sampling technique on stunting data from the Sicanang Medan Health Center. Analysis was carried out with descriptive, bivariate and multivariate analysis using multiple logistic regression analysis test. The analysis was carried out to find the most influential risk factors for the incidence of stunting cases at the Sicanang Health Center. The results of multivariate analysis by considering confounding factors showed that the most influential factors on the incidence of stunting were mothers who married too young (aOR = 0.64; 95% CI = 0.21-1.49; p-value = 0.046) and child spacing below 2 years young (aOR = 1.53; 95% CI = 0.22-2.83; p-value = 0.023).